Mercury isotope evidence for a non-volcanic origin of Hg spikes at the Ordovician-Silurian boundary, South China - Shen, Jun; Algeo, Thomas J.; Feng, Qinglai (Earth and planetary science letters, 2022)
Ordovician-Silurian transition (OST) sections of South China contain extremely high mercury (Hg) concentrations (>1000 ppb) of uncertain provenance. The main hypotheses concerning their origin are: (1) contemporaneous elevated seawater Hg concentrations (e.g., due to volcanogenic inputs) combined with normal Hg-uptake processes by marine sediments, and (2) normal seawater Hg concentrations combined with enhanced Hg uptake by marine sediments (e.g., due to strong adsorption by sulfides). Here, we investigate Hg isotopes, which are a promising tool to track the sources of Hg in sediments, in OST strata of the Jiaoye drillcore from the Yangtze Platform of South China. Black shales and pyritic beds exhibit mass-independent fractionations of odd Hg isotopes (odd-MIF, i.e., Δ199Hg) of +0.13±0.05‰ and +0.13±0.03‰, respectively. These values are similar to those of modern and ancient marine sediments, supporting a seawater source of Hg in the study units and providing evidence against a volcanic source. We infer that the extreme Hg enrichment of the OST beds was due to elevated rates of Hg uptake from seawater through adsorption to pyrite. Local environmental conditions (e.g., intense euxinia and microbial sulfate reduction) played a dominant role in Hg enrichment of OST strata in South China. •Hg isotope data for highly Hg-enriched Ordovician-Silurian boundary strata, China.•(Chalcophilic) Hg taken up by pyrite under anoxic bottomwater conditions.•Hg peaks around OSB were sourced from seawater, not from volcanic inputs.•Mass-independent fractionation (Δ199Hg=+0.13±0.03‰) supports seawater source.